2006
DOI: 10.1592/phco.26.11.1537
|View full text |Cite
|
Sign up to set email alerts
|

Newer Pharmacotherapy in Patients Undergoing Percutaneous Coronary Interventions: A Guide for Pharmacists and Other Health Care Professionals

Abstract: Significant advances in pharmacotherapy for patients undergoing percutaneous coronary intervention (PCI) have occurred during the past decade, including the introduction and approval of new antithrombin and antiplatelet therapies, as well as modifications in dosing, administration, and/or duration of older pharmacotherapy regimens. Also, off-label (i.e., not approved by the United States Food and Drug Administration) use of certain agents has become common. Given the novel nature of these agents and the nuance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…298,299,779,780 Medications that require dosage adjustments in patients with CKD include eptifibatide, tirofiban, bivalirudin, enoxaparin, and fondaparinux. 781 …”
Section: Class I 1 In Patients Undergoing Pci the Glomerular Filtramentioning
confidence: 99%
“…298,299,779,780 Medications that require dosage adjustments in patients with CKD include eptifibatide, tirofiban, bivalirudin, enoxaparin, and fondaparinux. 781 …”
Section: Class I 1 In Patients Undergoing Pci the Glomerular Filtramentioning
confidence: 99%
“…62 Both are selective noncompetitive inhibitors of the P2Y 12 receptor. The active metabolites of ticlopidine and clopidogrel induce a permanent defect that involves a single platelet-signaling pathway for the lifetime of the cell via cumulative inhibition at low doses in a manner similar to the pharmacodynamics of aspirin.…”
Section: Ticlopidine and Clopidogrelmentioning
confidence: 99%
“…64 Poor tolerance of larger loading doses (Ͼ500 mg) precludes this approach to achieve earlier platelet inhibition. 62 Diarrhea, nausea, and vomiting are common side effects (30% to 50%). Skin rash is also a frequent problem.…”
Section: Ticlopidine and Clopidogrelmentioning
confidence: 99%
“…Clinically relevant antiplatelet activity at the standard dose (250 mg twice daily, oral) occurs at 24–48 h, peaking at 3–5 days. The unacceptably high incidence of GI side effects (30%–50% vomiting, nausea, and diarrhea) precluded the use of a higher loading dose (500 mg daily, oral) 16,17. Neutropenia as a side effect of ticlopidine was first noted in phase III trials and was subsequently shown to be as high as 2.4% 18.…”
Section: Antiplatelet Agentsmentioning
confidence: 99%